PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. PLN (PERSERO) UPT KARAWANG - Adhe Oktapiani Sopian; Suroso; Flora Patricia Anggela (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study investigates the influence of occupational safety and health (OSH) and work discipline on employee productivity. Employing a quantitative verificative design, the research involves 41 field division employees of PT. PLN (Persero) UPT Karawang, selected using a saturated sampling technique where the entire population serves as the sample. Data processing applied multiple linear regression analysis. The stages of analysis encompassed instrument validity and reliability testing, classical assumption tests, multiple linear regression calculations, and hypothesis testing through t-tests and F-tests. Additionally, the determination coefficient was calculated to assess the predictive capability of independent variables on the dependent variable. The findings indicate that the application of OSH positively impacts employee productivity, and work discipline also demonstrates a positive correlation with productivity. Together, OSH and work discipline significantly affect employee productivity at PT. PLN (Persero) UPT Karawang. Verificative analysis and multiple regression were utilized to conclude and validate hypotheses. These results suggest that prioritizing OSH and discipline leads to higher productivity levels. However, further studies are recommended to identify other variables contributing to employee productivity. This research emphasizes the importance of focusing on OSH and work discipline to enhance organizational productivity effectively.